Traditional chinese medicine in Canada: An indigenous perspective - Honoré France; Carmen Rodriguez (Wolters Kluwer Health/LWW, 2019)
This paper summarizes the practice of traditional Chinese medicine (TCM) in Canada by exploring why so many indigenous people are drawn to it. We present a brief history of TCM in Canada, including its acceptance by 5 of the 10 provinces in Canada as one of the medical approaches, accepted and regulated by the government. Chinese philosophy embedded in TCM is compared to indigenous philosophy, and there is a description of some of the plants and animals used as remedies in indigenous folk medicine. In addition, there is a short description of how TCM psychology parallels some practices in indigenous psychology.